Who on Earth Can Work from Home? - Garrote Sanchez, Daniel; Gomez Parra, Nicolas; Ozden, Caglar; Rijkers, Bob; Viollaz, Mariana; Winkler, Hernan (World Bank, Washington, DC, 2020)
This paper presents new estimates of the share of jobs that can be performed from home. The analysis is based on the task content of occupations, their information and communications technology requirements, and the availability of internet access by country and income groupings. Globally, one of every five jobs can be performed from home. The ability to telework is correlated with income. In low-income countries, only one of every 26 jobs can be done from home. Failing to account for internet access yields upward biased estimates of the resilience of poor countries, lagging regions, and poor workers. Since better paid workers are more likely to be able to work from home, COVID-19 is likely to exacerbate inequality, especially in richer countries where better paid and educated workers are insulated from the shock. The overall labor market burden of COVID-19 is bound to be larger in poor countries, where only a small share of workers can work from home and social protection systems are weaker. Across the globe, young, poorly educated workers and those on temporary contracts are least likely to be able to work from home and more vulnerable to the labor market shocks from COVID-19.